Acute Pulmonary Embolism after Discharge: Duration of Therapy and Follow-up Testing - Becattini, Cecilia; Franco, Laura; Agnelli, Giancarlo (Seminars in Respiratory and Critical Care Medicine, 2017)
Pulmonary embolism (PE) is a frequent cause of death and serious disability with a risk extending far beyond the acute phase of the disease. Anticoagulant treatment reduces the risk for death and recurrent VTE after a first PE. The optimal duration of anticoagulation after a first episode of PE remains controversial and should be made on an individual basis, balancing the estimated risk for recurrence without anticoagulant treatment against bleeding risk under anticoagulation. Current recommendations on duration of anticoagulation are based on a 3% per year risk of major bleeding expected during long-term warfarin treatment. Anticoagulant therapy should be discontinued after the initial 3 to 6 months in those patients who had the first episode in association with temporary risk factors. After 3 to 6 months of anticoagulant treatment, patients with a first unprovoked event and an estimated low risk for bleeding complications should be evaluated for indefinite treatment on an individualized basis. None of the clinical prediction models for recurrent VTE are able to actually drive duration of anticoagulation. If the favorable safety profile of direct oral anticoagulants from clinical trials would be confirmed in real-life, extension of anticoagulation could be reconsidered in large proportions of patients after an unprovoked PE. The most feared late sequela of PE is chronic thromboembolic pulmonary hypertension. Although there has been progress in both the diagnosis and management of this disease in recent years, further data are needed to provide recommendations regarding long-term follow-up after PE.
Keywords: pulmonary embolism; anticoagulants; dabigatran; rivaroxaban; apixaban; edoxaban